Pemanfaatan E-Commerce Dalam Upaya Meningkatkan Penjualan Bunga Hias Komunitas Lestari Cyclop di Jayapura - Hastutie Noor Andriati (The Community Engagement Journal, 2020)
Based on direct observation of the micro and small scale business actors, they have not been fully used internet as a promotion or sales tool. Whereas throughout accessing various social media is an opportunity to support increasing business sales because the product is more recognized by the public, so that it can increase the likelihood of transactions taking place. Recently, small business actor who is still doing conventional marketplace and have not used information technology such as the internet is a florist, Lestari Cycloop. Lestari Cycloop business group is a group of ornamental plants and cut flowers domiciled around the Cycloop Area. On that basis, this dedication is carried out to help the business group of Lestari Cycloop in conducting online sales/promotion (e-commerce). During the mentoring process partners who are assisted feel very helped by this devotional activity. In addition to facilitating the creation of digital media that if it helps the promotion of products, this community service activity can increase sales profit after being marketed through the empowerment of social media such as FB, IG, and WAG.